Compiler : (Pearson/Addison Wesley, 2007)
This book provides the foundation for understanding the theory and pracitce of compilers. Revised and updated, it reflects the current state of compilation. Every chapter has been completely revised to reflect developments in software engineering, programming languages, and computer architecture that have occurred since 1986, when the last edition published. The authors, recognizing that few readers will ever go on to construct a compiler, retain their focus on the broader set of problems faced in software design and software development. Computer scientists, developers, and aspiring students that want to learn how to build, maintain, and execute a compiler for a major programming language.